DEVELOPMENT OF THE DOWN PASSING EXERCISE TOOL FUTSAL EXTRACURRICULAR JUNIOR HIGH SCHOOL STUDENTS - Sabarudddin Yunis Bangun; Raja Syaifullah Sihombing; Rafli Hadinata (Universitas Negeri Medan, 2022)
The purpose of this study was to develop a tool for passing down training for junior high school students in extracurricular Futsal. The subjects in this study were extracurricular Futsal students at Harapan Mekar Middle School, Medan. The research instrument used was a questionnaire/questionnaire. The results of the development research data were obtained through expert evaluations and group trials through filling out questionnaires. The results of the material expert validators as a whole in Phase I obtained results of 86% and in Phase II obtained results of 90%. Categorized as